The interval ejection fraction: a cineangiographic and radionuclide study - Kemper, A J; Bianco, J A; Shulman, R M; Folland, E D; Parisi, A F; Tow, D E (Circulation (New York, N.Y.), 1982)
To evaluate the clinical usefulness of the first-third ejection fraction (1/3 EF) for detecting patients with coronary artery disease (CAD), resting contrast ventriculography and first-pass radionuclide angiography with a high-count-rate, multicrystal camera system were performed in 47 subjects: 22 normal controls (group 1) and 25 patients with clinically stable angina pectoris and severe CAD (mean 2.3 vessels) without (group 2, n = 12) and with (group 3, n = 13) resting wall motion abnormalities. By contrast angiography, only group 3 had depressed global EF or 1/3 EF compared with control (global EF: group 1,0.71 +/- 0.09; group 2, 0.67 +/- 0.09 [NS]; group 3,049 +/- 0.05 [p less than 0.01 vs groups 1 and 2]; 1/3 EF: group 1,0.29% +/- 0.06;' group 2, 0.28 +/- 0.05 [NS]; group 3,0.22 +/- 0.05 [p less than 0.02 vs groups 1 and 2]). Whereas 11 of 25 CAD patients had global EF outside the normal range, only two of 25 had depressed 1/3 EF. Both had left ventricular asynergy and a depressed global EF. Studies performed using first-pass radionuclide angiography revealed similar results i.e., only four of 25 CAD patients, all with left ventricular asynergy and depressed global EF, had depressed 1/3 EF values. A wide range of 1/3 EF values was found in normal subjects by both techniques. Thus, the ejection fraction during the first third of systole at rest is of limited value for detecting patients with CAD.